MULTIMEDIALITà€ E SCULTURA DIGITALE FANNO RIVIVERE L’ATHENA NIKE - MediaGEO, Redazione (Archeomatica, 2013)
The Establishment Sorgente Group, Institution for Arts and Culturesupported by the real estate-fi nance group Sorgente, launched inJanuary 2013 a project of great impact, unique in the Italian museum:an intuition of the Vice President, Paola Mainetti, supportedby curator for Archaeology Valentina Nicolucci, has transformed thefi rst exhibition on the statue of Athena Nike in a multimedia installationthat draws the visitor on a journey back in time to the Greeceof Pericles.